Modern trends in the development of competitive activities in aikido in Russia - Sobyanin, F. I.; Beketov, O. V.; Malakhov, V. A.; Filatov, M. S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify trends in the development of aikido in Russia based on the analysis of the results of competitive activity.